Tumor odontogénico epitelial calcificante reporte de tres casos y revisión de la literatura - Francisco Levi Duque Serna; Tatiana Isabel López Gaviria; Raúl Jiménez Gómez (Universidad de Antioquia, 2001)
Three cases of calcifying epithelial odontogenic tumor are reported and the recent literature is reviewed. The first patient, a 20 years old male, had a mandibular right mass, extending from canine to third molar, of slow growth and measuring 8x3x4 cm. There was no mobility and pulp vitality was present radiographically, the lesion was radio-lucent with central radiopacity. Enucleation and curettage were performed, after two years of follow up there was no recurrence. The second patient, a 36 year old female, consulted because of a mandibular lesion that compromised from the second bicuspid to the posterior border of the left mandibular ramus. The molars had been previously extracted and the radiographic image was similar to the first case. An 8 year old boy was the third patient, in which a 4x3x2 cm., palatal mass appeared after the extraction of an upper left first deciduos molar. Radiographs showed an ill defined radio-lucent lesion with radiopacity. No treatment was performed; the patient returned 6 months later with a mass of 8x6x4.5 cm., that compromised from the upper lateral incisor to the first permanent molar, all the teeth in the area were affected. A hemimaxillectomy was performed and with three reconstructive surgeries the oral-nasal communication was obliterated.